Analisis Kinerja Petugas Apron Movement Control (AMC) Dalam Pengoperasian Fasilitas Aviobridge di Bandar Udara Internasional Jenderal Ahmad Yani Semarang - Alifian Amirul Akbar; Ika Fathin Resti Martanti (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
After the Covid-19 pandemic has resulted in an increase in the number of aviobridge users. This is an obstacle for the AMC unit because the number of personnel on duty is very limited. To create good service, it is necessary to regulate the performance of good officers. The purpose of this study was to find out the application of the SOP for operating aviobridge, setting the performance of officers, the obstacles experienced by officers, and efforts/strategies for the problems experienced by AMC officers in operating aviobridge. The research design used is qualitative research. The research was conducted from March to April 2023 at Jenderal Ahmad Yani International Airport, Semarang. This study used 3 data collection techniques, namely observation, interview, and documentation techniques. Data analysis techniques in this study used data reduction techniques, data presentation, and conclusions. The results showed that the performance of AMC officers in operating the aviobridge had followed several SOP guidelines, but several officers had not fully implemented attribute procedures such as the use of ear muffs, goggles and safety shoes. The obstacles in operating the aviobridge are technical problems and limited personnel. These problems make the jobdesc of the officers irregular, plotting the changing work schedules of the officers, and causing the operation of the aviobridge at some times to experience mild delays. The efforts made by the AMC unit are by coordinating between units and maximizing personnel performance.